The Use of a Bony Kernel for CT-Brain in Head Trauma - Bove, Michele (My University, 2017)
Introduction: Head trauma is a common cause of mortality and computed tomography of the brain (CT-Brain) remains the gold standard investigation for head injuries. Locally a bony kernel is reconstructed routinely in addition to a brain kernel on the assumption that it improves fracture detection. This additional kernel increases scanning time, reporting time and storage required on picture archiving and communication systems (PACS). Aim: The aim was to determine if a bony kernel is superior to a brain kernel for detecting fractures of the skull. Objectives: Objectives were to document patient and fracture characteristics seen locally, to identify patient and fracture characteristics that may require the use of a bony kernel and to determine if the bony kernel needs to be stored on a PACS. Methods: A retrospective study was undertaken. 216 CT-Brains were collected with associated demographic data and mechanisms of injury, attempting to match fracture cases to controls. Two expert readers in consensus formed a gold standard by evaluating all studies. The majority decision between three general readers was then used to test for a difference between the kernels for fracture detection. Results: There was no significant difference in the sensitivity or specificity between the two kernels (p=0.74 and 1.00). Interpersonal violence between adult males and pedestrian vehicle accidents in ambulant children were noted to be common indications for CT-Brain requests locally. Conclusions: The use of only the brain kernel is advised in adults, resulting in decreased scanner time, reporting time and required storage space on PACS. Further research is suggested to investigate its use in younger patients.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Diagnostic Radiology Johannesburg, 2017.
Keywords: Bony Kernel; Craniocerebral Trauma (Head Trauma)